Kajian Hermeneutika dalam Sjair Iblis - Fajar Hardi Muhammad; Jefrizal Jefrizal (Masyarakat Pernaskahan Nusantara (The Indonesian Association for Nusantara Manuscripts, Manassa), 2019)
Abstract: Sjair Iblis is one of the manuscripts which is a religious group containing the teachings and beliefs of Muslims. Poetry of the Devil is included in one of the manuscripts that the author and the author do not know about, or better known as